Does self-medication reduce medical expenditure among the middle-aged and elderly population? A four-wave longitudinal study in China - Zheng, Zehao; Feng, Zhanchun; Zhang, Donglan; Sun, Xiaobo; Dong, Dong; Luo, Youxi; Feng, Da (Frontiers in Public Health, 2023)
Introduction Self-medication has a high prevalence in the middle-aged and elderly population in China. Despite the published evidence demonstrating the economic benefits of self-medication, limited research has addressed the relationship between self-medication and individual medical expenditures, especially within the Chinese population. This study examined the effect of self-medication on individual medical expenditures in China and analyzed the heterogeneity between outpatient and inpatient cases. Methods We conducted a panel data analysis using data from four waves of the China Health and Retirement Longitudinal Study (CHARLS). Two-part mixed-effect models were implemented to estimate the effect of self-medication on total outpatient and inpatient expenses and out-of-pocket (OOP) costs, where mixed-effects logit regression was used as the first part, and generalized linear mixed models with log link and gamma distribution was used as the second part. Results We identified 72,041 responses representing 24,641 individuals, of which 13,185 responses incurred outpatient expenses and 9,003 responses incurred inpatient costs. Controlling for all covariates, we found that self-medication behaviors were significantly associated with a higher probability of outpatient service utilization (OR = 1.250, 95% CI = 0.179 to 0.269; P < 0.001), but displayed no significant association with outpatient expenses. Respondents who had taken self-medication were less likely to use inpatient services (OR = 0.865, 95% CI = −0.201 to −0.089; P < 0.001), and their inpatient expenses were significantly reduced by 9.4% (P < 0.001). Inpatient OOP costs were significantly reduced by 10.7% (P < 0.001), and outpatient OOP costs were significantly increased by 11.3% (P < 0.001) among respondents who had self-medicated. Conclusions This study allowed us to identify the economic value of self-medication among the middle-aged and elderly population in China. Future work should guide the middle-aged and elderly to take responsible self-medication to reduce their economic burden.